Analysis of action of device with spring pins for picking up of retted flax straw - V. G. Chernikov; V. Yu. Romanenko (Сельскохозяйственные машины и технологии)
Weather conditions in flax cultivation areas during harvesting time can be characterized with high rainfalls, relative humidity and, in some areas, extremely low temperature. Clogging of fields with stones, grass germination through flax swaths, often an absence of homogeneity on length and thickness of straw in swaths require working out new devices for straw lifting. Existing devices for picking up do not provide a high-quality lifting of flax swaths and have a low coefficient of reliability of the process. Researches and experimental-design works were carried out to create a constructive-technological scheme of the picking up device of cylindrical type with spring-loaded rigid pins. The mathematical model of the device operation when a pin touching an obstacle. The condition of balance of the mechanism under which the pin of a cilinder will operate technological process of picking up of retted flax straw without action of the safety device (spring) was described. The offered method of calculation of operation of this device was introduced in a common flax swath lifter-turners